1973
DOI: 10.1084/jem.138.3.686
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Clotting System in Cell-Mediated Hypersensitivity

Abstract: Indirect evidence has implicated the coagulation system in the pathogenesis of cell-mediated hypersensitivity. Thus, anticoagulants have been shown to inhibit the expression of a variety of delayed-type reactions in vivo in animals including classic tuberculin skin hypersensitivity (1-5) and allergic contact dermatitis (2), the ocular reaction to tuberculin (6), and the antigen-induced maerophage disappearance reaction (1, 7). Moreover, a variety of agents that interfere with different steps in the clotting se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…It was demonstrated that fibrinogen and fibrin contribute to inflammation by inducing leukocyte migration (22)(23)(24). Later, in vitro and in vivo studies demonstrated that fibrin(ogen) alters inflammation not only by affecting leukocyte migration, but also by directly modulating the inflammatory response of leukocytes and ECs via an increased cytokine/chemokine response.…”
Section: Inflammatory Potential Of Fibrinogen and Fibrinmentioning
confidence: 99%
“…It was demonstrated that fibrinogen and fibrin contribute to inflammation by inducing leukocyte migration (22)(23)(24). Later, in vitro and in vivo studies demonstrated that fibrin(ogen) alters inflammation not only by affecting leukocyte migration, but also by directly modulating the inflammatory response of leukocytes and ECs via an increased cytokine/chemokine response.…”
Section: Inflammatory Potential Of Fibrinogen and Fibrinmentioning
confidence: 99%
“…We have looked, therefore, for the deposition of Ig and C3 in vessels, or other parts of freshly grafted skin, during the period when it is insensitive to MARS. Anti-graft serum, either MARS or RARS that had been absorbed with mouse tissues, was injected intraperitoneally at a dose of 0.5 ml, and the grafts were removed 2-4 h later and prepared for examination with fluoresceinated antisera as described elsewhere (6). Rabbit antiserum was used in some experiments because it was thought to facilitate the distinction between endogenous and injected immunoglobulins in this experimental system.…”
Section: Influence Of Surgical Dressings and The Regimen Of Lmmunosupmentioning
confidence: 99%
“…Grafts were excised from their hosts and cryostat sections of them were prepared for studies with fluorescent antisera as described previously (6). Fluoresceinconjugated antibodies reactive with rabbit IgG, mouse IgG, mouse C3, chicken IgG, or mouse serum albumin were obtained from N. L. Cappel Laboratories (Cochranville, Pa.).…”
mentioning
confidence: 99%
“…Accordingly, injury, infection, and (auto)immunity are associated with extravascular fibrin(ogen) (3)(4)(5)(6).…”
mentioning
confidence: 99%